Productivity enhancement of laser powder bed fusion using compensated shelled geometries and hot isostatic pressing - Anton Du Plessis; Bharat Yelamanchi; Christian Fischer; James Miller; Chad Beamer; Kirk Rogers; Pedro Cortes; Johan Els; Eric MacDonald (Advances in Industrial and Manufacturing Engineering, 2021)
In laser powder bed fusion (L-PBF), the mechanical performance and especially fatigue properties of fabricated parts are significantly improved by hot isostatic pressing (HIP) as the density increases (pores are closed) and the microstructure improves. HIP ensures consistent and defect-free material, and consequently, this high temperature and high pressure process is often a requirement for safety-critical aerospace applications. The use of HIP to directly consolidate intentionally-unmelted interior powder in a L-PBF part was recently demonstrated. By confining the laser melting to only the outer shell (contour) of the structure, L-PBF production times can be dramatically reduced. A subsequent HIP cycle, which may be mandatory for reliability reasons, and therefore does not add additional costs, is then used to densify the entire structure. Production rates and energy efficiencies can therefore be improved in this way. This study explores the effect of relying on the HIP process to consolidate interior sections of test coupons, for which micro computed tomography (microCT), process simulation and tensile tests were conducted. MicroCT of coupons with varying shell thicknesses identify the minimum shell thickness required; and provide indications of the shrinkage ratio as a function of powder content relative to shell thickness. Preliminary results are included in which the shrinkage can be compensated for during design, by way of a “bloated cube” which collapses to a nominal cube geometry after HIP. The mechanical evaluation of the consolidated shelled parts indicates that their tensile performance is equivalent to those observed on fully dense printed parts. Up to an order of magnitude faster build rates are possible and any resulting shrinkage or distortion can be offset at design.